Species of the Maera-clade collected from Japan. Part 1: genera Maeropsis Chevreux, 1919 and Orientomaera gen. nov. (Crustacea: Amphipoda: Maeridae) - Ariyama, Hiroyuki (Zootaxa, 2018)
The Maera-clade is a group of maerid amphipod genera which has neither a falcate mandibular palp nor medially setose inner plates of maxillae 1 and 2. Two species of Maeropsis Chevreux, 1919 and four species of Orientomaera gen. nov. included in the clade, are described from Japan. Maeropsis okinawensis sp. nov. is described, based on collections from Okinawa Prefecture. It resembles M. cobia Krapp-Schickel, 2009, M. paphavasitae Wongkamhaeng, Coleman & Pholpunthin, 2013, and M. serratipalma (Nagata, 1965). This new species differs from the latter three species in the long uropod 3. Maeropsis serratipalma is redescribed and newly recorded from Kanagawa, Osaka and Wakayama Prefectures. The new genus, Orientomaera, is described and is characterized by the mandibular palp article 1 without a distal tooth and the oblique palm of the gnathopod 2 with many robust setae. Orientomaera comprises four species: O. brevispina (Kim & Kim, 1991) comb. nov. from Iwate, Fukui, Kyoto and Wakayama Prefectures and Ariake Sea; O. decipiens sp. nov. from Osaka and Wakayama Prefectures; O. obliquua sp. nov. from Osaka and Wakayama Prefectures; O. rotundicoxa sp. nov. from Kanagawa and Wakayama Prefectures. These species can be distinguished from one another by the coxa 1, the gnathopod 2 propodus, the pereopod 6 basis and the telson. Keys to species of Maeropsis and Orientomaera in the world are provided.